Discursive Construction of Female Sexuality in the Game VA11 Hall-A: Cyberpunk Bartender Action - Fatiha Nefissa Kinandera; Junaidi Junaidi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2025)
This paper examines the representation of female sexuality in the visual novel game VA-11 Hall-A: Cyberpunk Bartender Action. Previous research on female sexuality in video games has primarily focused on visuals, leaving a gap in language-based analysis. This study employs Critical Discourse Analysis (CDA), using Fairclough's (2001) three-dimensional model and Nussbaum’s (1995) objectification theory to examine four dialogues from the game. The results indicate efforts to challenge the traditional stance on sexuality, however further linguistic analysis reveals contradictions to these intentions. The analysis also highlights an emphasis on physical attractiveness and fragmented body parts for the enjoyment of others. This emphasis is achieved through language shaped by the Western Anime subculture community of practice, aligning character appeal with player expectation. The article concludes that the sexualized portrayal of female characters aligns with dominant discourses on sexuality, contributing to the perpetuation of this cultural phenomenon.